Assessment of first and second degree relatives of individuals with bipolar disorder shows increased genetic risk scores in both affected relatives and young At‐Risk Individuals. Issue 7 (16th July 2015) - Fullerton, Janice M.; Koller, Daniel L.; Edenberg, Howard J.; Foroud, Tatiana; Liu, Hai; Glowinski, Anne L.; McInnis, Melvin G.; Wilcox, Holly C.; Frankland, Andrew; Roberts, Gloria; Schofield, Peter R.; Mitchell, Philip B.; et al.
Abstract : Recent studies have revealed the polygenic nature of bipolar disorder (BP), and identified common risk variants associated with illness. However, the role of common polygenic risk in multiplex families has not previously been examined. The present study examined 249 European‐ancestry families from the NIMH Genetics Initiative sample, comparing subjects with narrowly defined BP (excluding bipolar II and recurrent unipolar depression; n = 601) and their adult relatives without BP (n = 695). Unrelated adult controls (n = 266) were from the NIMH TGEN control dataset. We also examined a prospective cohort of young (12–30 years) offspring and siblings of individuals with BPI and BPII disorder (at risk; n = 367) and psychiatrically screened controls (n = 229), ascertained from five sites in the US and Australia and assessed with standardized clinical protocols. Thirty‐two disease‐associated SNPs from the PGC‐BP Working Group report (2011) were genotyped and additive polygenic risk scores (PRS) derived. We show increased PRS in adult cases compared to unrelated controls ( P  = 3.4 × 10 −5, AUC = 0.60). In families with a high‐polygenic load (PRS score ≥32 in two or more subjects), PRS distinguished cases with BPI/SAB from other relatives ( P  = 0.014, RR = 1.32). Secondly, a higher PRS was observed in at‐risk youth, regardless of affected status, compared to unrelated controls (GEE‐χ 2  = 5.15, P  = 0.012). This report is the first to explore common polygenic risk in multiplex families, albeit using only a small number of robustly associated risk variants. We show that individuals with BP have a higher load of common disease‐associated variants than unrelated controls and first‐degree relatives, and illustrate the potential utility of PRS assessment in a family context. © 2015 The Authors. American Journal of Medical Genetics Part B: Neuropsychiatric Genetics Published by Wiley Periodicals, Inc.